In search of myths & heroes [videorecording (DVD)] - Jeffs, Jeremy; Wood, Michael, 1948-; Smith, Sean (PBS Home Video, 2005)
Follows Michael Wood as he travels in search of the truth behind four famous legends. Explores not only the historical past and literal truth of these myths, but also the mythic past and archetypal stories behind them. Examines the Biblical myth of the Queen of Sheba, an exotic and mysterious woman of power who, with King Solomon, plays a key role in the founding myths of the modern states of Israel and Ethiopia. Traces the Celtic legend of King Arthur and its role in British literature. Asks whether the legendary Shangri-La as depicted in James Hilton's Lost horizon could have its roots in Indian views of Tibet or in the Tibetan Buddhist stories of the land of Shambhala, a paradise behind the Himalayas. Discusses the Greek hero Jason and his quest for the golden fleece.